A label-free impedimetric sensor for the detection of an amphetamine-type derivative based on cucurbit[7]uril-mediated three-dimensional AuNPs - Hongjie Li; Xiaojun Hu; Jialin Zhao; Kwangnak Koh; Hongxia Chen (Electrochemistry Communications, 2019)
The abuse of amphetamine-type stimulants (ATS) has increased rapidly and so development of an easy, cheap and sensitive ATS sensor is of great importance. A facile label-free impedimetric sensor was fabricated using cucurbit[7]uril (CB[7]) as a recognition molecule to bind ATS. The presence of CB[7] enables the formation of three-dimensional AuNP structures (3D-AuNPs@CB[7]) which were characterized by Fourier transform infrared reflection spectroscopy, scanning electron microscopy and transmission electron microscopy. Due to the large effective area and high electronic transmission of 3D-AuNPs@CB[7], the 3D-AuNPs@CB[7]-modified electrodes produce 63 times the signal enhancement at the limit of detection compared with using CB[7] directly. In addition, the fabricated impedimetric sensor can accurately detect an amphetamine-type derivative in artificial urine and serum samples. Combining the properties of 3D nanostructures with a macrocyclic molecule, 3D-AuNPs@CB[7] offers a simple and sensitive platform for the detection of ATS. Keywords: Amphetamine-type derivative, Cucurbit[7]uril, Host–guest recognition, 3D-AuNPs